SEXUAL REPRODUCTION IN DERMATOPHYTES - Metin, Banu (Mycopathologia, 2016)
Sexual reproduction is a rich source of genetic variation and commonly observed among fungi. Basically two different modes of sexual reproduction are observed in fungi, namely heterothallism where two compatible mating types are required to undergo mating and homothallism in which the organism is self-fertile. The genomic region governing the process of sexual reproduction and sex determination is called the mating type (MAT) locus. In filamentous ascomycetes including dermatophytes, the MAT locus harbors two different transcription factor genes in two different mating types. This review focuses on sexual reproduction and the structure of the MAT locus in dermatophytes. The reproductive modes and the observed mating types are summarized for different phylogenetic clades of dermatophytes. In addition, the question of whether or not unisexual reproduction, an interesting form of homothallism, may be the sexual reproduction mode especially in anthropophilic dermatophytes is raised.